Environmental sustainability policy within Australian Olympic sport organisations. Issue 1 (2nd January 2023) - Cury, Rubiana; Kennelly, Millicent; Howes, Michael
ABSTRACT: The 2032 Brisbane Olympic Games commitment to deliver a 'climate-positive' Games raises concerns about the current environmental actions of Australian Olympic sport organisations. This study adapts a policy assessment framework, founded on environmental policy integration (EPI), to analyse the responses of Australian Olympic sport organisations to environmental sustainability. The integration of environmental considerations into sport policy is arguably critical to helping the sport industry transition to sustainable operations. However, an analysis of official documents found that the environmental responses of Australian Olympic sport organisations are limited and insufficient. It is argued that sport organisations need to develop more comprehensive mitigation and adaptation goals, change strategic directions, and integrate environmental policies into their mainstream activities. This transition should be supported by environmental impact and climate vulnerability assessments as well existing sport specific international frameworks (e.g., UN Sport for Climate Action Framework) and sustainability policies of international sports federations. The assessment framework used here has the potential to support the monitoring and evaluation of environmental policy integration within sport.